ESTABLISHMENT OF ACCOUNTING SYSTEM IN FARMER ECONOMIC FARMING - A.T.Mamajonov; R.Abdijamilov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the author discusses the organization and need for accounting systems in diversified farms, including their problems and solutions.